2019
DOI: 10.1016/j.pepi.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for seismic phase detection and picking in the aftershock zone of 2008 M7.9 Wenchuan Earthquake

Abstract: The increasing volume of seismic data from long-term continuous monitoring motivates the development of algorithms based on convolutional neural network (CNN) for faster and more reliable phase detection and picking. However, many less studied regions lack a significant amount of labeled events needed for traditional CNN approaches. In this paper, we present a CNN-based Phase-Identification Classifier (CPIC) designed for phase detection and picking on small to medium sized training datasets. When trained on 30… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 38 publications
1
61
0
3
Order By: Relevance
“…8 ). To compare the performances, we applied three deep-learning (DetNet 5 , Yews 4 , and CRED 7 ) detectors and one traditional (STA/LTA 11 ) detector to the same test set (Table 1 ). We should acknowledge that there is a level of tuning involved in each of these approaches (traditional and deep-learning detectors/pickers), and that the performance can vary based on this tuning.…”
Section: Resultsmentioning
confidence: 99%
“…8 ). To compare the performances, we applied three deep-learning (DetNet 5 , Yews 4 , and CRED 7 ) detectors and one traditional (STA/LTA 11 ) detector to the same test set (Table 1 ). We should acknowledge that there is a level of tuning involved in each of these approaches (traditional and deep-learning detectors/pickers), and that the performance can vary based on this tuning.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [115] trained two separate convolutional networks to pick P and S arrival times, on a database of over 700000 picks in Japan. Zhu et al [113] also utlized on a CNN to study the aftershock sequences of the 2008 M W 7.9 Wenchuan Earthquake. For all studies, results in testing were found to outperfom existing methods.…”
Section: Phase Picking and Polarity Determinationmentioning
confidence: 99%
“…Interestingly, models for phase picking appear to generalize better than models trained to detect earthquakes. Two recent studies report that their algorithms generalize well to regions outside of the training area, either without finetuning [115], or with minimal finetuning [113]. While this improved generalization could be attributed to larger training sets or model specificities, it might be the case that earthquake detection is intrinsically a more challenging problem in terms of generalization due to models indirectly learning specific Green's functions.…”
Section: Phase Picking and Polarity Determinationmentioning
confidence: 99%
See 2 more Smart Citations